CAPACITY AND TRANSFORMATION OF THE ROLE OF UNEXPECTED EXPENDITURE (BTT) IN REGIONAL FISCAL UNCERTAINTY: A SYSTEMATIC LITERATURE REVIEW - Fransiskus Lucky Arif Wicaksana; Alfitri; Raniasa Putra (RADJA PUBLIKA, 2026)
Unexpected Expenditure ( BTT) is instrument fiscal in Budget Regional Income and Expenditure (APBD) which is designed For respond condition emergency and uncertainty that is not can predicted . Although own role strategic as buffer fiscal area , various study show findings that are still fragmented related effectiveness and implementation of BTT. Research This aim For synthesize existing literature to understand​ dynamics regulation , transformation role , capacity fiscal , as well as governance challenges​ in implementation of BTT in government area . The method used is a Systematic Literature Review (SLR) by following PRISMA protocol . Search process literature done through the Google Scholar and Scopus databases using Publish or Perish instrument with range publication 2020–2025 . Of the 635 identified documents , the selection process produced 25 articles that meet the requirements criteria inclusion For analyzed . The data was analyzed use approach synthesis thematic that produces four theme main , namely : dynamics regulation and compliance administrative , transformation BTT's role in multi- disaster response , capacity fiscal and performance budget , as well as governance challenges​ operational . Research results show that BTT has experience transformation from the budget post passive become instrument more fiscal​ adaptive in respond various crisis , including disaster natural and non- natural . However , the effectiveness its implementation Still face various obstacle structural like volatility regulations , limitations capacity execution bureaucracy , validity of recipient data benefits , as well as limitations competence source Power humans . In addition , the non-cumulative design of the BTT causes remainder budget No can accumulated as a reserve fund term long . Therefore that , is necessary reorientation policies and strengthening governance capacity so that BTT can functioning optimally as​ instrument resilience fiscal area .